Influence of Ni and ZrO2 contents on sintering and mechanical properties of WC-2wt.%ZrO2-1wt.%Ni composites. Issue 9 (15th June 2019) - Zhao, Ziyou; Zhu, Degui; Gao, Yu; Lv, Lan; Liao, Nan; Jiang, Xiaosong; Luo, Zhiping
Abstract: WC-2wt.%ZrO2 -1wt.%Ni composites were prepared by vacuum pressureless sintering (VPS) and post-hot isostatic pressing (post-HIP). The microstructure, phase composition, densification, hardness, fracture toughness, and flexural strength of composites with different Ni and ZrO2 contents were systematically investigated. The results show that WC-Ni and WC-ZrO2 -Ni composites prepared by VPS can be densified by the addition of a small amount of Ni as the binder phase. Moreover, the densities of the composites can be further enhanced i.e. the composites are rendered nearly fully dense following HIP while the grains remain fine without obvious growth. The binder Ni and ZrO2 phases are uniformly distributed in the WC matrix and exhibit high bonding strength with it. The hardness, fracture toughness, and flexural strength of the WC-ZrO2 -Ni composites following HIP could reach 22.4 GPa, 12.0 MPa m 1/2, and 1101.2 MPa, respectively. Based on the influence of the Ni and ZrO2 contents on the microstructures and mechanical properties of the WC-2wt.%ZrO2 -1wt.%Ni composites, the fracture mechanism was determined to be governed by the phase transformation of ZrO2 that led to the development of some micro-cracks followed by deflection, bridging, and branching of the cracks to improve fracture toughness. The composites are mainly composed of elongated triangular prismatic WC grains and ZrO2 phases, and hence the fracture mode can change such that transgranular fracture becomes the main fracture mode accompanied by a small amount of intergranular fracture. Thus, the flexural strength of the composites can be improved.